Comparison of FISH, RFLP and agar dilution methods for testing clarithromycin resistance of Helicobacter pylori - Çiftci, İhsan Hakkı; Uğraş, Meltem; Acartürk, Gürsel; Aşık, Gülşah; Şafak, Birol; Dilek, Fatma Hüsniye (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Clarithromycin resistance is an important factor of Helicobacter pylori (H. pylori) eradication failure in adults and children. There are some tests to determine resistance such as restriction fragment length polimorphism (RFLP), fluorescence in situ hibridisation (FISH), PCR and (culture) agar dilution. Clarithromycin resistance is reported between 16.8%-48.2% in Turkey using PCR, 18% in Japan using RFLP. The aim of the study is to compare the efficacy of FISH, RFLP and culture. Materials and Methods: Patients with gastric complaint underwent endoscopic examination. H. pylori status of all patients was tested with urea breath test. Gastric biopsy samples obtained from adult patients and children were studied. Each tissue was analised with FISH, PCR-RFLP anda gar dilution. Results: A total 100 patients were positive by UBT and histology for H. pylori. Tissues from 89 adults and 11 children were evaluated. According to FISH and RFLP clarithromycin resistance was 26% and 16% respectively. Among 100 patients H. pylori was cultured in 52 tissue samples, among these samples 7 were resistant to clarithromycin. There was strong correlation between the results of FISH and RFLP; RFLP and culture; and FISH and culture. Conclusion: There is a high ratio of clarithromycin resistance in the studied population. All 3 tests are valuable, but FISH seems to be more sensitive among these tests. We suggest FISH should be used for detecting clarithromycin resistance among H. pylori infected patients before eradication therapy.